Mobile health in the specific management of first-episode psychosis: a systematic literature review - Maechling, Claire; Yrondi, Antoine; Cambon, Amandine (Frontiers in Psychiatry, 2023)
Purpose – The purpose of this systematic literature review is to assess the therapeutic efficacy of mobile health methods in the management of patients with first-episode psychosis (FEP). Method – The participants are patients with FEP. The interventions are smartphone applications. The studies assess the preliminary efficacy of various types of application. Results – One study found that monitoring symptoms minimised relapses, visits to A&E and hospital admissions, while one study showed a decrease in positive psychotic symptoms. One study found an improvement in anxiety symptoms and two studies noted an improvement in psychotic symptoms. One study demonstrated its efficacy in helping participants return to studying and employment and one study reported improved motivation. Conclusion – The studies suggest that mobile applications have potential value in the management of young patients with FEP through the use of various assessment and intervention tools. This systematic review has several limitations due to the lack of randomised controlled studies available in the literature.